Physical properties of near-Earth asteroids with a low delta-v: Survey of target candidates for the Hayabusa2 mission. (12th November 2018) - Hasegawa, Sunao; Kuroda, Daisuke; Kitazato, Kohei; Kasuga, Toshihiro; Sekiguchi, Tomohiko; Takato, Naruhisa; Aoki, Kentaro; Arai, Akira; Choi, Young-Jun; Fuse, Tetsuharu; Hanayama, Hidekazu; Hattori, Takashi; et al.
Abstract: Sample return from the near-Earth asteroid known as 25143 Itokawa was conducted as part of the Hayabusa mission, with a large number of scientific findings being derived from the returned samples. Following the Hayabusa mission, Hayabusa2 was planned, targeting sample return from a primitive asteroid. The primary target body of Hayabusa2 was asteroid 162173 Ryugu; however, it was also necessary to gather physical information for backup target selection. Therefore, we examined five asteroids spectroscopically, 43 asteroids spectrophotometrically, and 41 asteroids through periodic analysis. Hence, the physical properties of 74 near-Earth asteroids were obtained, which helped the Hayabusa2 backup target search, and also furthered understanding of the physical properties of individual asteroids and their origins.